Strategi Inovatif Dalam Pengelolaan Sumber Daya Manusia: Meningkatkan Kinerja Organisasi Di Era Digital - Fahmi Rizal; Zahara Tussoleha Rony (Jurnal Ekonomi Manajemen Sistem Informasi, 2024)
This journal discusses innovative strategies that can be applied in human resource management (HRM) to enhance organizational performance in the digital era. With rapid changes in technology and the business environment, organizations need to develop innovative approaches in managing their human resources. The article explores various innovative strategies, including the adoption of cutting edge technology, employee skill development, and adaptation to organizational cultural changes. The implementation of these innovative strategies can help organizations remain relevant and competitive in the evolving market.